Physical and Antibacterial Properties of Peppermint Essential Oil Loaded Poly (ε-caprolactone) (PCL) Electrospun Fiber Mats for Wound Healing - Unalan, Irem; Slavik, Benedikt; Buettner, Andrea; Goldmann, Wolfgang H.; Frank, Gerhard; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2019)
The aim of this study was to fabricate and characterize various concentrations of peppermint essential oil (PEP) loaded on poly(ɛ-caprolactone) (PCL) electrospun fiber mats for wound healing applications, where PEP was intended to impart antibacterial activity to the fibers. SEM images illustrated that the morphology of all electrospun fiber mats was smooth, uniform and bead-free. The average fiber diameter was reduced by the addition of PEP from 1.6±0.1 to 1.0±0.2 µm. Functional groups of the fibers were determined by Raman spectroscopy. Gas chromatography-mass spectroscopy (GC-MS) analysis demonstrated the actual PEP content in the samples. In vitro degradation was determined by measuring weight loss and their morphology change, showing that the electrospun fibers slightly degraded by the addition of PEP. The wettability of PCL and PEP loaded electrospun fiber mats was measured by determining contact angle and it was shown that wettability increased with the incorporation of PEP. The antimicrobial activity results revealed that PEP loaded PCL electrospun fiber mats exhibited inhibition against Staphylococcus aureus (gram-positive) and Escherichia coli (gram-negative) bacteria. Our findings showed for the first time PEP loaded PCL electrospun fiber mats with antibiotic-free antibacterial activity as promising candidates for wound healing applications.